Multicomponent polyurethane-carbon black composite as piezoresistive sensor - Sousa, Eliraldrin Amorin; Castro Lima, Thalita Hellen; Silva Arlindo, Elen Poliani; Sanches, Alex Otavio [UNESP]; Sakamoto, Walter Katsumi [UNESP]; Fuzari-Junior, Gilberto de Campos (Springer, 2020)
Composite of carbon black (CB) dispersed into a multicomponent polyurethane matrix combines the good mechanical properties of the polymer, such as elasticity, with the electrical property of the conducting particles. Electrical current-voltage (I x V) analysis found the percolation threshold through the sample surface to be between 0.6 and 0.8 vol%. Below the percolation threshold concentration (p(c)), the effect of the Coulomb potential is accentuated on the CB dispersion, while in the region over p(c), the London-van der Waals potential is important. The repeatability in the piezoresistive behavior was observed under the application of several loading cycles. The gauge factors obtained were 4.9 and 2.0 for samples with 0.8 and 1.0 vol% of CB, respectively. The results indicate that the material can be used as a piezoresistive sensor.
Keywords: Polyurethane; Carbon black; Piezoresistance